Evolution of the Processed Tomato Sector in Portugal and Spain: Comparative Analysis - de Oliveira, Maria de Fátima Martins Lorena; Cepeda, Mariano Suárez de; Bernabéu, Rodolfo (Emirates Journal of Food and Agriculture, 2019)
World production of processed tomato has shifted from the traditional producing countries to others that were previously importers, thereby increasing competition between companies and slowing down agro-industrial and trade growth. Portugal, one of the world’s leading producers of processed tomato has not been immune to this trend, as witnessed by its decline in international competitiveness over the period from 1981 to 2013. The aim of the present study is thus twofold. On the one hand, using various standardized indicators, the determinants of the business competitiveness of processed tomato are analyzed, and, on the other, we perform a comparative analysis between Spain and Portugal. The standardized indicators used in this study are the Revealed Comparative Advantage (RCA), the Revealed Symmetric Comparative Advantage (RSCA) and the Grubel-Lloyd indicator (GL). The results show that price continues to be the primary determinant in processed tomato exports. Specifically, while trade in tomato paste in Portugal is inter-industry, trade in other tomato products is horizontal intra-industry in nature. In conclusion, the relationship between agro-industrial development and technological innovation in Portugal and Spain is key to reducing costs as a strategy to bring competitive and sustainable products to the market.